PENGARUH HUMAN RELATION, PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA GURU MTsN 2 ACEH TIMUR GAMPONG JALAN KECAMATAN IDI RAYEUK - Nelvita Nesca Putri; Agus Arianto; Zikrillah (An Nuqud Journal of Islamic Economics, 2026)
This study aims to examine the influence of human relations, training, and career development on teachers' performance at MTsN 2 East Aceh, Gampong Jalan, Idi Rayeuk District. Teacher performance plays a crucial role in improving the quality of education; therefore, various organizational factors are needed to enhance teachers' professionalism and productivity. This research employed a quantitative approach using a survey method. The population consisted of all teachers at MTsN 2 East Aceh, and a saturated sampling technique was applied, in which all members of the population were selected as respondents. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression after passing the validity, reliability, and classical assumption tests. The findings reveal that, partially, human relations have a positive and significant effect on teachers' performance. Likewise, training has a positive and significant effect on teachers' performance, while career development also exerts a positive and significant influence on teachers' performance. Simultaneously, human relations, training, and career development significantly affect teachers' performance. These findings indicate that harmonious interpersonal relationships, continuous professional training, and well-structured career development opportunities are essential factors in enhancing teachers' performance. Therefore, the school management is encouraged to foster a collaborative work environment, improve the quality of training programs, and establish a systematic career development framework to support sustainable improvements in educational quality.